Quantifying the roles of environmental, seasonal, and genome size variation in the expression of medicinally valuable compounds in Helichrysum kraussii Sch.Bip - Oberlander, Kenneth Carl (University of Pretoria, 2025)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2025.